An in-silico based multi epitope vaccine construction of flagellin protein opposing Helicobacter Pylori bacteria (H. Pylori) - Akhter, Tahamina (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2024.